Morfología y ecología de algunas Eleocharis R. Brown (Cyperaceae) cubanas - Zavaro Pérez, Carlos Alberto (1995)
Some of the most important morphological patterns in Cuban species of the genus Eleocharis are discussed, linked when possible with their adaptative value. A dichotomic key for the identification of the Cuban species is included.